Evaluación de la eficiencia energética del sistema eléctrico del proceso productivo de la empresa de lácteos “Soprab” de la ciudad de Ambato, en el año 2012 - 2013. Diseño de un plan de gestión para el uso eficiente de la energía eléctrica. - Mayorga Pérez, Méntor Fabián (2018)
The current and prospective development of industry and services, in an open and globalized economy, requires actions aimed at reducing costs and increasing competitiveness in a friendly way with the environment, generally in small and medium industries, the cost of implementing new technologies has provoked the problem about the use of obsolete equipment and energetically inefficient which leads to additional costs unnecessary for the energy input misused. Thus, there is the "Soprab" dairy industry in Ambato, so that the costs of electric energy consumption have become an increasingly significant item in the final costs of the products. The main objective of research work, it was to elaborate a methodologically and technical plan of defined actions that lead to improve the use of electric energy, identifying all the opportunities to reduce costs by this input. The research is contextualized in the search and identification of opportunities to improve the energy use of the dairy industry based on the analysis period 2012-2013, the research in.situ was developed with relevant bibliographic support mainly focused on the final use of electric energy in the which involves the power factor, control of demand and consumption, the main factors within an electric payment. The compilation and analysis of the data show the real diagnosis that allow the structuring of a management plan that will reduce 8% the invoiced value of the electric energy consumption with an investment amortized in 1,6 years, from one comes to become an economic resource for the company, finally, some recommendations and suggestions are described.